Development of Quality Index Method (QIM) scheme for spiny lobster (Panulirus argus, Latreille, 1804) stored in ice. (January 2015) - Gonçalves, Alex Augusto; de Lima, José Ticiano Arruda Ximenes; de Paula, Francisca Elizangela Rodrigues
Abstract: The objective of this study was to evaluate the freshness of spiny lobster ( Panulirus argus ) stored on ice up to 18 days. Changes during storage were observed with sensory evaluation (Quality Index Method – QIM), pH, total volatile basic nitrogen (TVB-N), trimethylamine nitrogen (TMA-N), and microbiological analyses (total mesophilic and psychrotrophic count). The maximum shelf life of spiny lobster stored in flake ice at 1 ± 0.2 °C was determined with loss of freshness (sensorial, physico-chemical and microbiological evaluations). High correlation R 2  = 0.922 between Quality Index (QI) and storage time at 1 °C was verified. QI ranged from zero (maximum freshness) to 15 (total loss of freshness) and reached the acceptable limit for consumption (QI = 9.54), which corresponds to a period of 10 days. The microbiological results showed an increase of psychrotrophic count along the storage time. TVB-N ranged from 5.23 to 20.31 mg 100 g −1, TMA-N from 1.07 to 5.72 mg 100 −1 and pH from 6.91 to 7.19 in the first and 18th day of storage, respectively. It is suggested that spiny lobster has to be fresh and acceptable for consumption by cooling up to 10 days. Highlights: Sensory evaluation is one of the most often used methods for assessing lobster freshness. Freshness is a key element in the quality assessment of lobster by consumers. The Quality Index Method (QIM) is a sensory evaluation method based upon a scheme. QIM is an excellent tool to teach inexperienced people to evaluate lobster. It is expected that QIM scheme be adopted as the official method for lobster inspection around the world.